Rekonstruksi Hukum Khitan Perempuan Perspektif Mashlahah - siska Syah (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
This article focuses on the views of prominent figures who consider female circumcision inhumane because of its health impacts and its basis in gender discrimination, giving the impression that these figures are absolutely opposed to the Sharia ruling on female circumcision. The research question is: How can the mashlahah perspective on female circumcision be applied through study of scholars’ texts and medical explanations to reconstruct the legal ruling on female circumcision? The author employs literature review method supported by empirical data. The data types and sources utilized follow a qualitative approach, yielding descriptive data. The research findings indicate that Imam Abu Hanifah, Yusuf al-Qardhawi and Wahbah Az-Zuhaili rule that female circumcision is makrumah; Imam Malik and Imam Ahmad consider it sunnah; while Imam Shafi’i and the majority of the Salaf deem it obligatory. Medically, female circumcision is permissible. Its benefits include hygiene, purity and balancing sexual desire by reducing excessive sensitivity to optimize the duration of intercourse; thus, female circumcision falls under al-mashlahah tahsiniyah and is part of Islamic law.